Bis{2-[2-(1H-indol-3-yl)ethyliminomethyl]phenolato-κ(2) N,O}nickel(II) N,N-dimethylformamide disolvate - Ali, Hapipah M. (International Union of Crystallography, 2008)
The Ni atom in the title compound, [Ni(C(17)H(15)N(2)O)(2)]·2C(3)H(7)NO, lies on a twofold rotation axis. It is N,O-chelated by the deprotonated Schiff base 2-[2-(1H-indol-3-yl)ethyliminomethyl]phenolate ligand in a square-planar coordination environment. The molecule is linked to a solvent molecule by an indole–dimethylformamide N—H⋯O hydrogen bond.